Connecting Histories : Francophone Caribbean Writers Interrogating Their Past - Thomas, Bonnie, 1975- (Book collections on Project MUSE., 2017)
"The francophone Caribbean boasts a veritable treasure trove of literary gems. Distinguished by innovative, elegant writing and thought-provoking methods of engaging with questions of history and identity, this exciting body of work demands attention. Its authors treat the traumatic legacies of shared and personal histories that pervade the Caribbean experience in striking ways, enunciating a path towards reconciliation and healing. The creation of diverse personal narratives -- encompassing autobiography, autofiction, travel writing, and reflective essay -- remains characteristic of many Caribbean writers and offers poignant illustrations of the complex interchange between shared and personal pasts and how they affect individual lives. Through their historically informed autobiography, the authors in this study -- Maryse Conde, Gisele Pineau, Patrick Chamoiseau, Edwidge Danticat, and Dany Laferriere -- offer compelling insights into confronting, coming to terms with, and reconciling their past. The employment of personal narratives as the vehicle to carry out this investigation points to a tension evident in these writers' reflections, which constantly move between the collective and the personal; their past is an inescapably complex, rhizomatic network that extends beyond the notion of a single, private life. These contemporary authors from the three francophone Caribbean islands of Martinique, Guadeloupe, and Haiti intertwine their personal memories with reflections on the histories of their homelands and on the European and North American countries they adopt through choice or necessity, thereby revealing a multitude of deep connections that illuminate distinct francophone Caribbean experiences"--